Application of laser remelting process on the Zr-Cu based alloy composite. (April 2018) - Wang, Huei-Sen; Chen, Hou-Guang; Liu, Yi-Ting; Shian-Ching Jang, Jason
Abstract: In this study, a 1.0 mm thick (Zr48 Cu32 Al8 Ag8, Ta4 )Si0.75 alloy composite (AC) plate was laser remelted (LR) by employing the Nd:YAG laser technique. To fully remelt the plate, a two-sided welding process with preselected parameters was employed. The microstructure, mechanical (microhardness), thermal properties, and corrosion resistance (potentiodynamic polarization) of the laser remelted alloy composite (LR-AC), the Zr-Cu AC (with the crystalline structure), and the Zr-Cu based bulk metallic glass composite (BMGC, the same composition as the AC. The amorphous matrix is produced by a rapid cooling rate) were then investigated and compared. The test results show that after the laser remelting processes, the LR-AC consisted of an amorphous matrix and reinforced phase, Ta, in the remelted areas, which is similar to the BMGC; however, the volume fractions and grain size of the micro-sized reinforced phase, Ta, in the LR-AC were reduced. When compared to those of the BMGC, the GFA indices of LR-AC were slightly improved. For the hardness tests, LR-AC showed a similar hardness to that of the BMGC; however, a higher value was obtained when compared to that of the AC. Furthermore, the LR-AC exhibits a lower Icorr (a slower corrosion rate), which is attributed to the amorphous matrix and less micro-sized Ta content, eliminating corrosion occurring between the Ta and the matrix of the alloy. Highlights: Zr-Cu alloy composite (AC) was produced at a slow cooling rate. The properties of CA could be improved using laser remelting process. Hardness of the laser remelted CA (LR-CA) is similar to that of the Zr-Cu BMGC. GFA and corrosion rate of the LR-CA are improved, compared to those of the BMGC.